Pengembangan Program Supervisi Akademik Berbasis ADDIE untuk Meningkatkan Keterampilan Mengajar Guru - D, Hamidah; Saputri, Lilis; Nurjanah, Baiti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to develop a practical and effective academic supervision program to improve the teaching skills of teachers at Bintang Langkat Private High School. This type of research is a development research, or Research and Development, and is designed to follow the stages of the ADDIE development model: analysis, design, development, implementation, and evaluation. The data collection methods used in this study are validity testing by media experts, design experts, and material experts as well as a small-scale trial with 3 teachers and a large-scale trial with 10 teachers at Bintang Langkat Private High School. This program was designed using a descriptive quantitative approach. The instruments used in this study include a validation questionnaire from experts to assess the level of validity, as well as questionnaires aimed at teachers and users to evaluate aspects of practicality and effectiveness. The results of the study revealed that the quality of the product in terms of validity is categorized as very valid. The average assessment from material experts, media experts, and design experts achieved an overall score of 88%. Based on a questionnaire administered to 10 teachers at Bintang Langkat Private High School, the practicality aspect achieved an overall average score of 92.2%, meeting the criteria for very practicality. Furthermore, based on a questionnaire administered to 10 teachers at Bintang Langkat Private High School, the effectiveness aspect achieved an overall average score of 92.2%, meeting the criteria for very effective.